Phosphodiesterase 2 inhibition preferentially promotes NO/guanylyl cyclase/cGMP signaling to reverse the development of heart failure - Baliga, Reshma S. (Proc Natl Acad Sci U S A, 2018)
Heart failure (HF) is a shared manifestation of several cardiovascular pathologies, including hypertension and myocardial infarction, and a limited repertoire of treatment modalities entails that the associated morbidity and mortality remain high. Impaired nitric oxide (NO)/guanylyl cyclase (GC)/cyclic guanosine-3′,5′-monophosphate (cGMP) signaling, underpinned, in part, by up-regulation of cyclic nucleotide-hydrolyzing phosphodiesterase (PDE) isozymes, contributes to the pathogenesis of HF, and interventions targeted to enhancing cGMP have proven effective in preclinical models and patients. Numerous PDE isozymes coordinate the regulation of cardiac cGMP in the context of HF; PDE2 expression and activity are up-regulated in experimental and human HF, but a well-defined role for this isoform in pathogenesis has yet to be established, certainly in terms of cGMP signaling. Herein, using a selective pharmacological inhibitor of PDE2, BAY 60-7550, and transgenic mice lacking either NO-sensitive GC-1α (GC-1α(−/−)) or natriuretic peptide-responsive GC-A (GC-A(−/−)), we demonstrate that the blockade of PDE2 promotes cGMP signaling to offset the pathogenesis of experimental HF (induced by pressure overload or sympathetic hyperactivation), reversing the development of left ventricular hypertrophy, compromised contractility, and cardiac fibrosis. Moreover, we show that this beneficial pharmacodynamic profile is maintained in GC-A(−/−) mice but is absent in animals null for GC-1α or treated with a NO synthase inhibitor, revealing that PDE2 inhibition preferentially enhances NO/GC/cGMP signaling in the setting of HF to exert wide-ranging protection to preserve cardiac structure and function. These data substantiate the targeting of PDE2 in HF as a tangible approach to maximize myocardial cGMP signaling and enhancing therapy.